2019
DOI: 10.1108/bfj-07-2018-0470
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet adherence in emerging adults in Izmir

Abstract: Purpose The purpose of this paper is to evaluate the adherence and abandonment of the Turkish emerging adults in an Izmir University located at western Mediterranean coast of Turkey and to assess potential associations with anthropometric characteristics. Design/methodology/approach A cross-sectional survey (n=494, 18–27 years) carried out in 2017 among emerging adults in University. KIDMED Index was used to assess the degree of adherence Mediterranean Diet (MedDiet). The associations of KIDMED scores with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The transition from high school to college often implies important changes to environment and resources that might result in negative health lifestyles, including poor-quality diets [ 15 , 24 ]. A cross-sectional study conducted in the Turkish university students showed that residency was directly related to adherence to the MedDiet, supporting the theory that students who were living with family had more positive adherence compared to the students who were living away from their family homes [ 23 ]. In the current study, almost 42% of participants had poor or average adherence to the MedDiet, suggesting a need for nutrition interventions that focus on promoting healthy dietary habits in early adulthood.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The transition from high school to college often implies important changes to environment and resources that might result in negative health lifestyles, including poor-quality diets [ 15 , 24 ]. A cross-sectional study conducted in the Turkish university students showed that residency was directly related to adherence to the MedDiet, supporting the theory that students who were living with family had more positive adherence compared to the students who were living away from their family homes [ 23 ]. In the current study, almost 42% of participants had poor or average adherence to the MedDiet, suggesting a need for nutrition interventions that focus on promoting healthy dietary habits in early adulthood.…”
Section: Discussionmentioning
confidence: 85%
“…Based on their KIDMED scores, 58.4% of participants had a good adherence to the MedDiet. Worse scores were obtained by Stefan et al in a cohort of 276 college students from Croatia [ 17 ], and by Genc & Genc in emerging adults at a university on the western Mediterranean coast of Turkey [ 23 ]. Discrepancies can be attributed to differences in dietary habits among different countries.…”
Section: Discussionmentioning
confidence: 99%
“…According to El Ansari et al (2012), the student's transition from school to university coincides with changing living arrangements, which might also result in a reorientation of eating behaviours and in an appropriate time for education on Nutrition with lasting healthier choices. Similarly, Genc and Genc (2019) found very low adherence to Mediterranean Diet, especially among the students who don't live together with their family during the education period.…”
Section: Resultsmentioning
confidence: 94%